AN OBSERVATIONAL STUDY TO EVALUATE BIOPHYSICAL PROFILE BY ULTRASONOGRAPHY. - Dr. Omprakash Khokhar (International Journal of Medical Science And Diagnosis Research, 2018)
Background- Maternal perception of fetal movements is one of the 1st signs of fetal life & is regarded as a manifestation of fetal well being. Methods- An observational study was conducted at Department of Radiodiagnosis ; S.P.Medical College And Associate Groups Of PBM Hospitals,Bikaner. Results-53% of the baby had evidence of fetal growth retardation,13% of baby had APGAR score less than 7,25% baby had abnormal cord. Conclusion -The foremost need in a pregnant woman complaining of reduced fetal movement is to exclude a fetal demise. Keywords- Biophysical Profile Score, Caesarean Section, Fetal Growth Retardation.